Moderation, a Divine Command and an Existential Tradition - Mohammad Zabihi (اخلاق وحیانی)
According to our religious teachings, the Quran is the book of guidance and salvation for mankind, thus, its immediate audience is also the mankind. Of course, its domain of influence is not restricted to mankind only since if mankind, who has become competent and worthy of the Dignitate Homenis, executes his Divine and humane obligations properly, not only he himself will find ultimate perfection, but many other beings will also benefit from the effects of this Revealed Book through him; this is because of the fact that an abundance of damages done to the natural world have been the consequences of mankind’s ill-treatment of the natural environment. Therefore, considering the unique stance of mankind in the creation- as he enjoys the Divine Laws and he has also become worthy of the reception of the Revealed Laws- the present study seeks to demonstrate that two of the most fundamental ethical principles are “moderation” and “temperance”, through making use of the religious texts, and in particular the holy Quran. The claim here is that if mankind, whose basic nature and structure is based on moderation, finds his ultimate form, then, in light of this biological and moral principle, not only he himself will find felicity- which is an ultimate human ideal- but also other beings (including his own kind and the rest of his inferior beings) will be protected from moral and environmental harms.